2017
DOI: 10.1080/00365521.2017.1304987
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effectiveness of vedolizumab in inflammatory bowel disease: a national study based on the Swedish National Quality Registry for Inflammatory Bowel Disease (SWIBREG)

Abstract: Vedolizumab-treated patients represent a treatment-refractory group. A long-term effect can be achieved, even beyond 1 year of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
77
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(97 citation statements)
references
References 30 publications
15
77
1
4
Order By: Relevance
“…To date, limited information on the effectiveness and safety of this drug in clinical practice is available (Table ). Furthermore, the long‐term benefit of vedolizumab in clinical practice is barely known, as there are only three studies that have evaluated the effectiveness of this agent after approximately 1 year follow‐up .…”
Section: Introductionmentioning
confidence: 99%
“…To date, limited information on the effectiveness and safety of this drug in clinical practice is available (Table ). Furthermore, the long‐term benefit of vedolizumab in clinical practice is barely known, as there are only three studies that have evaluated the effectiveness of this agent after approximately 1 year follow‐up .…”
Section: Introductionmentioning
confidence: 99%
“…Analyzing the data of 246 patients, the authors found that at the end of follow-up, 54% of Crohn's disease patients and 64% of ulcerative colitis patients were in clinical remission [19]. In comparison, our data show response rates of 60.7% in Crohn's disease patients and 52% in ulcerative colitis patients.…”
Section: Discussionmentioning
confidence: 60%
“…In comparison, our data show response rates of 60.7% in Crohn's disease patients and 52% in ulcerative colitis patients. In the Swedish study, 58% of the patients remained on vedolizumab after a median follow-up of 17 months [19]. In our cohort, after a median follow-up of 30 weeks plus 6.5 months, 54% of Crohn's disease patients remained on vedolizumab; after a median follow-up of 30 weeks plus [20].…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations